Neuroinflammation: targeting microglia for neuroprotection and repair after spinal cord injury - Cavalcanti, Roberta Ramos; Almeida, Fernanda Martins; Martinez, Ana Maria Blanco; Freria, Camila Marques (Frontiers in Immunology, 2025)
Neuroinflammation is a tightly regulated process essential for central nervous system (CNS) homeostasis, debris clearance, and defense against pathogens. Microglia, the resident immune cells of the CNS, are central to this response, supporting plasticity and repair under normal conditions. Following spinal cord injury (SCI), however, this response becomes amplified and dysregulated. Early microglial activation can be protective, but prolonged activation drives the release of pro-inflammatory and cytotoxic mediators that exacerbate secondary injury and hinder repair. Microglia also engage in complex crosstalk with astrocytes, oligodendrocytes, neurons, and infiltrating immune cells, orchestrating both protective and damaging processes. This dual and dynamic nature underscores their importance as both targets and modulators in SCI therapies. This review aims to examine the roles of microglia in SCI, summarizes SCI pathology, the specific roles of microglia and macrophages, and outlines translational efforts to modulate their activation, while also highlighting the barriers to clinical application. Evidence from preclinical studies and emerging therapeutic strategies, including pharmacological, cell-based, and exosome-based interventions, demonstrates the potential to reduce harmful inflammation, promote neuroprotection, and support functional recovery. Despite these advances, clinical translation remains limited, constrained by the heterogeneity of microglial responses, narrow therapeutic windows, and patient-specific variability. These challenges often lead to modest or inconsistent clinical outcomes. Future strategies will require precision, multi-targeted approaches that integrate microglial modulation with the preservation of the blood–brain barrier (BBB) and the regulation of peripheral immune infiltration. Harnessing the regenerative potential of microglia, guided by biomarker-based patient stratification and a deeper understanding of their dynamic roles, offers the most promising path toward meaningful recovery after SCI.